Can Countries Rely on Foreign Saving for Investment and Economic Development? - Eduardo Cavallo; Barry Eichengreen; Ugo Panizza (Inter-American Development Bank (IDB), 2016)
A surprisingly large number of countries have been able to finance a significant fraction of domestic investment using foreign finance for extended periods. While many of these episodes are in low-income countries where official finance is more important than private finance, this paper also identifies a number of episodes where a substantial fraction of domestic investment was financed via private capital inflows. That said, foreign savings are not a good substitute for domestic savings, since more often than not episodes of large and persistent current account deficits do not end happily. Rather, they end abruptly with compression of the current account, real exchange rate depreciation, and a sharp slowdown in investment. Summing over the deficit episode and its aftermath, growth is slower than when countries rely on domestic savings. The paper concludes that financing growth and investment out of foreign savings, while not impossible, is risky.
hdl:11319/7792
Keywords: F32; O16; 330; Current account; Growth; Volatility; Savings